Morphological comparison of Anisotremus interruptus (Gill, 1862) (Perciformes: Haemulidae) populations along the Tropical Eastern Pacific - Acevedo Álvarez, Edgar Adrián (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
The family Haemulidae is a marine fish group of ample distribution and of fishery importance that has been object of many studies through the Tropical Eastern Pacific (TEP). Phylogenetic studies on the species Anisotremus interruptus have revealed a high genetic diversity as well as divergence among its populations into the TEP, suggesting that its taxonomical diversity could be underestimated. Anisotremus interruptus possesses a wide distribution ranging from central Baja California Sur and Gulf of Mexico to northern Peru, including all oceanic islands except Clipperton. Recent genetic studies on this taxon indicate the presence of a species complex of at least three distinctive lineages. Under this premise, we performed a comparative study of the population-level meristic and morphometric variation of A. interruptus into the TEP, in order to evaluate and identify possible morphological features in support to the recent recognition of the genetically different populations. Our results provide evidence on the presence of two new species for the Revillagigedo and Galapagos archipelagos, respectively.

La familia Haemulidae es un grupo de peces marinos de amplia distribución e importancia pesquera que ha sido objeto de diversos estudios en el Pacífico oriental tropical (POT). Los estudios genéticos sobre la especie Anisotremus interruptus han revelado una importante diversidad genética, así como una divergencia importante entre sus poblaciones a lo largo del POT, lo que sugiere que su diversidad taxonómica podría estar subestimada. Anisotremus interruptus posee una amplia distribución que va desde la zona central de Baja California Sur, el Golfo de California hasta el norte de Perú, incluyendo todas las islas oceánicas, excepto Clipperton. Estudios genéticos recientes sobre este taxón indican la presencia de un complejo de al menos tres linajes distintivos. Bajo esta premisa, realizamos un estudio comparativo de la variación merística y morfométrica a nivel poblacional de A. interruptus en el TEP, con el fin de evaluar e identificar posibles rasgos morfológicos que apoyen el reciente reconocimiento de las poblaciones genéticamente diferentes. Nuestros resultados proporcionan pruebas sobre la presencia de dos nuevas especies para los archipiélagos de Revillagigedo y Galápagos, respectivamente.
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FB-R-M-2020-0320; Taxonomía; Morfometria; Merística; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1821